Stress in Angkola Batak Language: An Acoustic Phonetic Approach - Tengku, Syarfina; Hasibuan, Alika Sandra; Sinaga, Lusiana (Linguistik, Terjemahan, Sastra (LINGTERSA), 2023)
The purpose of this study was to analyze the prosody of stress in declarative utterances of the Angkola Batak language using an acoustic phonetic approach. This research used an experimental phonetic approach, namely by performing manipulations aimed at determining the effects of manipulation on the observed behavior of individuals (Latipun, 2002). Experimental measurements of speech sounds were carried out using spectrum analysis using a computer. The recordings used came from a Sony ICD-PX 470 recorder in WAV format, and Praat software version 6.0.54 was used to analyze suprasegmental or prosodic features. The suprasegmental or prosodic features analyzed include pitch, intensity, and duration of speech. The results of this study showed that the stress position of declarative utterances in the Angkola Batak language was located at the beginning of the word or the first syllable. Like the word mangan, which consisted of two syllables, namely the words ma and ngan, the emphasis occured at the beginning of the word or the first syllable, namely ma with a frequency of 175.9 Hz, a duration of 0.582 seconds and an intensity of 73.99 decibels. Then the word utte which consisted of two syllables, namely the words ut and te, the emphasis occured at the beginning of the word or the first syllable, namely ut with a frequency of 323.6 Hz, a duration of 0.167 seconds and an intensity of 65.4 decibels. In addition, with the same findings in words consisting of three syllables, such as the word mamasu, which consisted of three syllables, namely the words ma, ma and su, the emphasis occured in the first syllable, namely ma with a frequency of 200.3 Hz, a duration of 0.198 seconds and an intensity of 72.65 decibels. The stress on the first syllable in declarative sentences was based on the high frequency value produced by Angkola Batak native speakers.